2010
DOI: 10.1007/s11060-010-0322-6
|View full text |Cite
|
Sign up to set email alerts
|

Kitten-transmitted Bordetella bronchiseptica infection in a patient receiving temozolomide for glioblastoma

Abstract: Bordetella bronchiseptica is a gram negative coccobacillus that can be transmitted from domestic animals and cause severe infections in immunocompromised patients. A 56-year-old man with a left parietal glioblastoma was treated with resection, radiation and concomitant and adjuvant temozolomide chemotherapy. He received bevacizumab for progression, and dose dense metronomic temozolomide was added for additional progression. He developed chronic cough and was diagnosed with B. bronchiseptica infection. This is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…In a review of the literature, the majority of patients infected with B. bronchiseptica had at least one predisposing disease such as acute lymphocytic leukemia,3 chronic lymphocytic leukemia,4,5 lymphopenia associated with temolozolide treatment for glioblastoma,6 cystic fibrosis7 or had undergone hematopoietic stem cell transplantation (HSCT),8,9 or lung transplantation 10. Our study adds three new cases of B. bronchiseptica pneumonia to the current literature, which includes a patient with malignant thymoma, a patient with adenocarcinoma of unknown primary origin with brain metastases, and a patient with a history of lung and supraglottic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In a review of the literature, the majority of patients infected with B. bronchiseptica had at least one predisposing disease such as acute lymphocytic leukemia,3 chronic lymphocytic leukemia,4,5 lymphopenia associated with temolozolide treatment for glioblastoma,6 cystic fibrosis7 or had undergone hematopoietic stem cell transplantation (HSCT),8,9 or lung transplantation 10. Our study adds three new cases of B. bronchiseptica pneumonia to the current literature, which includes a patient with malignant thymoma, a patient with adenocarcinoma of unknown primary origin with brain metastases, and a patient with a history of lung and supraglottic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen cases of opportunistic infection related to immunosuppression were reported [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. The confounding effect of other chemotherapeutic agents was excluded by demonstrating either the lack of temporal relationship or the nonoccurrence of toxicity on continuation of these agents.…”
Section: Uncommon Infectionmentioning
confidence: 99%
“…In the series by Yacoub et al [12], no clear transmission from pets can be assumed. Redelmann-Sidid et al [13] reported recently a patient with glioblastoma on temozolomide therapy with kitten-transmitted B. bronchoseptica infection. Wernli et al [7] summarized recently eight cases of B. bronchoseptica infection in human beings, the majority of whom had severe underlying disease and three of whom had been exposed to cats.…”
Section: Discussionmentioning
confidence: 99%
“…Pneumonia is the most common manifestation in human beings, however, reports on other infections such as one patient with liver cirrhosis and spontaneous bacterial peritonitis caused by B. bronchiseptica are available [9]. There is evidence that transmission through animal vectors plays a key role [7,8,[13][14][15][16]. Register et al [8] documented transmission of B. bronchiseptica from a cat to a patient with cystic fibrosis.…”
mentioning
confidence: 99%